The relationship of shock index, modified shock index, and age shock index with mortality in the intensive care unit (Annals of Medical Research, 2021)
Aim: Shock indexes are associated with clinical outcomes of patients, particularly in the emergency department. The present study aimed to evaluate the predictive capacity of Shock Index, Modified Shock Index, and Age Shock Index in terms of mortality in patients admitted to intensive care units.Material and Methods: All patients (aged >18 years) admitted to intensive care unit between January 01, 2018 and October 31, 2018 were included. Vital signs at the time of hospitalization were used to calculate Shock Index, Modified Shock Index, and Age Shock Index. Patients with shock were divided into three groups: Group 1 (septic shock), Group 2 (hypovolemic shock), and Group 3 (cardiogenic shock). The primary outcome was to evaluate intensive care unit mortality.Results: Mortality was 37% among 308 patients included in the study. Shock Index, Modified Shock Index, and Age Shock Index levels were significantly higher in patients with mortality (p 0.05). Shock Index, Modified Shock Index, and Age Shock Index levels were significantly higher than normal range in Group 1, 2, and 3 (p 0.05).Conclusion: All three shock indices were observed to be high in all patients with shock, and three shock indices were similarly significant in predicting mortality in patients admitted to intensive care units.
Keywords: Intensive care unit; shock index; modified shock index; age shock index; mortality.